ANALYSIS OF FACTORS AFFECTING PURCHASE INTENTION TO SALES OF FASHION PRODUCT THROUGH E-COMMERCE PLATFORMS IN BATAM CITY - Alamsyah, Abdur Rohim; Hasan, Golan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023DO - 10.24843/EEB.2023.v12.i08.p11, 2023)
The author conducted this study aimed to identify and analyze what factors can influence purchase intentions for fashion products on e-commerce platforms. In this case, the object of this study is the people who exist, especially in Batam City with an age range of 17 years and over who have the purchase intention to buy fashion products through an e-commerce platform. The independent variables used in this study are function values, social values, emotional values, price values ??and e-WOM. The dependent variable used is purchase intention with trust as a mediation. This study applies an explanatory method with a quantitative approach in collecting data and the technique used by the author is a purposive sampling technique with data analysis using the SmartPLS 3 software application. The results of this study identify the importance of price value, social value and e-WOM for a company in increasing trust in making purchase intentions for a product. If this trust is created, it will certainly bring up purchase intentions in consumers.